Reading Test—Sentence Comprehension: An Adapted Version of Lobrot's Lecture 3 Test for Brazilian Portuguese. (14th January 2016) - de Araújo Vilhena, Douglas; Sucena, Ana; Castro, São Luís; Pinheiro, Ângela Maria Vieira
Abstract : Our aim was to analyse the linguistic structure of the Lobrot's Lecture 3 (L3) reading test and to describe the procedure for its adaptation to a Brazilian cultural‐linguistic context. The resulting adapted version is called the Reading Test—Sentence Comprehension [Teste de Leitura: Compreensão de Sentenças (TELCS)] and was developed using the European Portuguese adaptation of L3 as a reference. The present study was conducted in seven steps: (1) classification of the response alternatives of L3 test; (2) adaptation of the original sentences into Brazilian Portuguese; (3) back‐translation; (4) adaptation of the distractors from TELCS; (5) configuration of TELCS; (6) pilot study; and (7) validation and standardization. In comparison with L3, TELCS included new linguistic and structural variables, such as frequency of occurrence of the distractors, gender neutrality and position of the target words. The instrument can be used for a collective screening or individual clinical administration purposes to evaluate the reading ability of second‐to‐fifth‐grade and 7‐to‐11‐year‐old students. Copyright © 2016 John Wiley & Sons, Ltd.